Amplitude visuoatencional, consciência fonêmica e desempenho em leitura: um estudo transversal com alunos do ensino fundamental - Sargiani, Renan de Almeida (2013)
Earlier studies showed that reading performance depends on phonemic awareness skills and visual attention span (VAS). Phonemic awareness refers to sensitivity and intentional control over the smallest speech sounds, i.e., phonemes. Visual attention span refers to the amount of distinct visual elements (letters) that can be processed simultaneously within a given set. There are hardly any studies on these two skills and their role in reading performance among Brazilian Portuguese speakers. This study aims at verifying (1) the existence of relationships between the skills of VAS and phonemic awareness and their relations with the reading performance of Brazilian children and (2) whether these relations would modify during their schooling years. The sample was made up of 48 students (1st, 3rd and 5th grade) from a public elementary school in Sao Paulo (Brazil). Children were assessed in three sessions through a battery of tasks which included single word reading, phonemic awareness, VAS, nonverbal IQ, verbal short-term memory and letter identification threshold. Results showed that VAS and phonemic awareness correlated with performance in reading of regular and irregular words and nonwords from 1st to 5th grade of elementary school. They also indicated that VAS and phonemic awareness play a more important role at the beginning of the learning of reading, i.e., in 1st grade, but continue to be of importance to reading ability in 3rd and 5th grade especially in reading of nonwords. It was also observed that there is a development of reading skills, phonemic awareness and visual attention span with the progress in schooling